PENGARUH KOMITMEN ORGANISASI, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN STIE PASAMAN - Wildan Wildan (Jurnal Apresiasi Ekonomi, 2016)
This research aims to show: (1) the Influence of Organizational Commitment, Work Motivation and Work Discipline toward Employees’ Performance simultaneously (2) the Influence of Organizational commitment, Work Motivation and Work Discipline toward Employees’ Performance partially. The population was all employees In STIE Pasaman about 36 people. Samples were taken from all of the population were 36 people. The dissemination of questionnaires to 36 respondents, it was only returned 35 pieces of questionnaires from 36 respondents. Methods of analysis were using multiple regression analysis. The result showed: 1) the Influence of Organizational commitment (X1), work motivation (X2), work discipline (X3) toward the Employee Performance simultaneously (Y) was approximately 0.519 with Sig. 0,000 F